The crisis of representative democracy and the tendencies towards a hyper-presidentialism, an analysis of the Mexican case - Wong Meraz, Víctor Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article analyzes one of the central issues for modern constitutionalism: the control of power. With the crisis provoked by COVID-19, it has put all the world's democratic institutions in check. This has caused the temptation of strong presidents to resurface, or even to reach out to authoritarian presidentialisms under the argument of being able to respond better to the challenge. The methodology used for this research will be qualitative, in the sense that the resulting analysis is based on the study in various texts of the famous metaconstitutional faculties that have had an impact on constitutional reality. Likewise, the results of 2018 will be analyzed, considering that it could detonate the meta-constitutional faculties of the Mexican resident. As a result of the research, the importance of the study of the constitutional debate in the Weimar Republic, during the Between Wars period, is proven. It is considered the most rigorous and has contributed the most to juridical sciences. There we can fall into the juridical positivism of Kelsen, the decisionism of Schmitt, the integrationist of Smend, or the methodology of the constitutional sciences of Heller.